Extending mercy to the gentiles the Jewish apocalyptic trajectory of Pauline discipleship - Harrigan, John P. 1977- (American Society of Missiology monograph series, 2023)
"Paul's discipleship agenda was defined by his native Jewish apocalyptic worldview. The novelties of his thought--namely, the death of Israel's Messiah, the unique gift of God's Spirit, and the intentional mission to the gentiles--seem to be framed within the common Jewish eschatological parameters of the day of the Lord, the judgment, the resurrection of the dead, and the messianic kingdom. Moreover, for Paul this eschatology was the primary driver of discipleship--comforting in the midst of tribulation, anchoring the gifts of the Spirit, and informing divine mission. Paul thus discipled the gentiles into the hope of Israel." --